ANALYSIS OF THE MOTIVATION THEORIES OF CONTENT: AN APPLICATION TO CHILE’S LABOR MARKET OF 2009 - Araya-Castillo, Luis (2014)
Currently, decision makers must understand the needs that motivate workers, becausethey focus on the needs that motivate to the workers. For this reason, the present studyhad used the factorial analysis of the principal components, in order to configure the maintheories of content. The findings validate these assumptions showing that these theoriesare interrelated, but at the same time, these differ in terms of the level of importance attributableto the needs. In this context, it is concluded that different theories of content motivationshare a set of assumptions about human needs, even of the cluster resulting (andrelative weights of the needs) are different.